The Effect of Therapeutic Essential Fragrance of Roses through Inhalation Treatment on the Pain Scale of Post Sectio Caesarea Patients - Gusti Lestari Handayani; Syamsul Ridjal; Abbasiah Abbasiah (Alliance oh Health Activists (AloHA), 2019)
In 2008, it was reported that the number of women giving birth with sectio caesarea (SC) increased 4 times compared to the last 10 years before. Childbirth figures in the United States as much as 35% of all childbirths, and in Asia as much as 28%. WHO reported that the incident of SC childbirth in developing countries occured about 10-15% of all types of labor. Childbirth with SC is not considered as a new thing for some mothers as well as the mothers from upper middle class. It is proved by the increasing of Indonesian SC childbirth of 5% to 20% in the last 20 years. There are some of the complications arising from the SC. One of those is the pain in the area of the incision. This study aimed to examine the effect of therapeutic essential fragrance of roses through inhalation treatment to the pain scale of SC post-surgery patients in obstetrics ward in the H. Abdul Manap hospitals, Jambi in 2013. This study used quasi-experimental research which was designed with one group pre test-post test. The data was collected using a verbal description scale (verbal response scale). Based on the results of the analysis showed that there was a significant reduction in patient pain scale after the treatment of roses essential inhalation was given (p-value = 0.003). Statistical test results showed that the optimal decline in patient pain scale before and after the treatment. That could be stated that the decline of the pain scale was optimal due to the decline from an average of 3.27 (fourth quartile) to 2.97 (second quartiles). The pain scale of post-surgery patients of sectio Caesarea before they had been given the rose essential inhalation treatment had an average pain scale between 3.05 to 3.48, conversely when they had the treatment resulted the decline of pain scale with the ranges from 2.97 to 3.25 which the lowest value scale was 2 and the highest was 4. It is suggested that the use of essential rose inhalation treatment could be an alternative in order to reduce the pain of sectio Caesarea post-surgery patiens and it is expected improving students proficiency in the non-pharmacological pain management. Keywords: Pain, Post sectio Caesarea, Therapeutic essential fragrance of roses, Inhalation treatment